Edukasi Bahaya Cyberbullying dan Pelatihan Teknik Self Control Dalam Bersosial Media - Nuryatin, Atin; Mulyati, Sri; Pratiwi, Rania Tania; Suryani, Yeyen; Rismayanti, Tesha; Tri, Agnesia (UNIB Press, 2025)
In this digital era, many people use social media as a means to convey their aspirations because of the aspect of freedom of opinion and expression. However, quite a few cyberbullying is carried out by abusing freedom of opinion, such as criticizing people, carrying out terror in the form of text messages, and other threatening things. This certainly has to be a common concern so that everyone can use social media wisely. Therefore, it is necessary to conduct further studies on the phenomenon of cyberbullying and appropriate handling through strengthening self-control in social media for all groups. This PKM activity was attended by 20 youth participants in Cipari Village. In this activity, participants are given a thorough understanding of cyberbullying and are given strengthening self-control techniques in using social media. Self-control is controlling behavior by considering the whole before deciding on something, so it can be said that control is related to how each participant can control their own behavior and emotions so that they are able to refrain from doing things that are prohibited. The results of this activity show that the majority of participants have sufficient cognitive understanding of cyberbullying and have insight between cognitive and emotional self-regulation in social media